What does the barrier index measure, and what it doesn't? Reactions to a recent article on the subject - Felsmann, Balázs; Vékony, András (Energy policy, 2023)
This comment reacts to Almeida, Esposito and van Zeben's (2022) critical assessment of the two-year length project on analysing barriers to entry in electricity and gas retail markets, commissioned by the European Commission in 2018. Our response follows the structure of their paper and answers several methodological and practical points the authors have criticized. We hope that our response clarifies some conceptual and methodological questions concerned and stimulates further academic debate on the appropriate usage of indices in comparison of different national circumstances and markets. •Measuring entry barriers.•Barrier Index.•Consequences vs. causes in composite indices.